Connective tissue disorder and high risk pregnancy: a case series with personalised external aortic root support (PEARS) - Claudia Montanaro; Polona Kacar; Giulia Iannaccone; John Pepper; Gurleen Wander; Christoph A. Nienaber; Andreas Hoschtitzky; Mario Petrou; Hannah Douglas; Mark R. Johnson; Roshni R. Patel; Isma Rafiq; et al. (Nature Communications)
Abstract Aortopathy including Marfan (MFS) and Loeys-Dietz syndrome (LDS) poses a high risk of aortic dissection, particularly during pregnancy and the puerperium. Current preventive measures of aortic root dilatation include medical therapy and prophylactic aortic root replacement. The Personalised External Aortic Root Support (PEARS) operation has been developed as an alternative surgical strategy to prevent aortic root dilatation and is now an established procedure with a good prognosis. However, outcomes in pregnant women are unknown. We present case series of nine successful pregnancies in seven women with aortopathy (6 MFS and 1 LDS) who underwent PEARS procedure prior to conception. At a mean follow-up of 4.3 years after delivery, there was no type A or B aortic dissections. Aortic dimensions remained stable, and no hypertensive disorders were observed. Although this is a small retrospective study, PEARS procedure may be a viable pre-conception surgical strategy for women with aortopathy, as an alternative to conventional aortic root surgery. Further studies are needed to conclude that PEARS could be a non-inferior or superior alternative to conventional aortic root surgery in these patients.